High-performance NASICON type oxide electrolyte and preparation method thereof
By adding polyoxygenate to the NASICON type oxide precursor, high-performance NASICON type oxide electrolyte is prepared, which solves the problems of low conductivity and excessive interface impedance, and achieves higher sodium ion conductivity and lower interface impedance.
Patent Information
- Application Number
- CN202411872179.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The existing NASICON type oxide electrolytes have problems with low conductivity and excessive interface impedance.
Polymethoxylates (POMs) are added to the NASICON type oxide precursor, and high-performance NASICON type oxide electrolyte is prepared by ball milling and calcining.
It effectively improves the sodium-philic properties and intrinsic ionic conductivity of NASICON solid electrolytes, reduces the interface impedance, and makes the interface impedance of the sodium symmetric half-cell at room temperature less than 20Ωcm2.
Smart Images

Figure CN119674200A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of energy storage, and in particular relates to a high-performance NASICON-type oxide electrolyte and a preparation method thereof. Background Art
[0002] With the development of society, the demand for energy is increasing, and the pollution of fossil energy is also making environmental problems more serious. Therefore, ion batteries have received great attention. However, the alcohol ester electrolyte used in ion batteries has serious safety hazards, forcing people to continue to look for safer battery systems to replace liquid batteries.
[0003] Solid-state batteries do not use liquid electrolytes, which effectively inhibits the formation of dendrites, making them have excellent safety performance. At the same time, alkali metals can be used as negative electrodes to greatly increase the theoretical specific capacity, so they have become the main research direction at present. Among them, the huge cost advantage of sodium salts makes it the most promising all-solid-state battery. The current main all-solid-state sodium ion electrolytes are divided into oxide electrolytes, halosulfide electrolytes and polymer electrolytes. NASICON-type oxide electrolytes have attracted people's attention due to their simple synthesis, high mechanical strength and good electrochemical stability, but their poor wetting properties with Na metal and low intrinsic ion conductivity still need to be improved.
[0004] Chinese patent document CN114361578A uses NASICON-type oxide ceramics as the matrix, and inorganic ferroelectric materials are evenly distributed at the grain boundaries of the NASICON-type oxide ceramic matrix. The ferroelectric modification improves the ionic conductivity of the electrolyte to a certain extent. On the one hand, the introduction of the inorganic ferroelectric phase accelerates the mass transfer at the grain boundaries during high-temperature sintering. On the other hand, due to the toughening effect of the inorganic ferroelectric phase, the mechanical properties of the ceramic matrix are improved, which can effectively inhibit the growth and extension of metal dendrites. However, the electrolyte still has the problem of excessive interface impedance, and the conductivity needs to be further improved. Summary of the invention
[0005] In order to solve the problems of low conductivity and excessive interface impedance in existing NASICON-type oxide electrolytes, the present invention provides a high-performance NASICON-type oxide electrolyte and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A high-performance NASICON-type oxide electrolyte is based on NASICON-type oxide and contains polyoxometalate accounting for 0.1-20%wt of the NASICON-type oxide.
[0008] Preferably, the NASICON type oxide Na3Zr2Si2PO 12 powder.
[0009] Preferably, the amount of polyoxometalate added is 0.5%-15wt%; further preferably, the amount added is 0.5%-12wt%, and further preferably, 4-10wt%.
[0010] Preferably, the polyoxometalate is selected from lanthanum strontium aluminate (SrLaAlO4), zinc chromate (CrO4Zn), strontium europium dysprosium aluminate (Sr 0.95 Eu 0.02 Dy 0.03 Al2O4), imidazole dichromate (C6H 10 At least one of Cr2N4O7), pyridinium chlorochromate (C5H6ClCrNO3), strontium chromate (CrO4Sr), sodium antimonate (NaO3Sb), lead chromate (CrO4Pb), barium molybdate (BaMoO4), sodium molybdate (MoNa2O4), and zinc tungstate (O4WZn). More preferably, strontium aluminate, europium dysprosium, pyridinium chlorochromate, imidazole dichromate, and sodium antimonate are used.
[0011] The present invention also provides a method for preparing the high-performance NASICON-type oxide, comprising weighing sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and polyoxometalate to obtain a mixed material, adding a ball milling agent, and ball milling the mixed material to obtain a mixed slurry; drying the mixed slurry and calcining it to obtain a NASICON solid electrolyte precursor, and finally pressing and sintering it to obtain a high-performance NASICON-type oxide electrolyte.
[0012] The mass ratio of sodium carbonate, zirconium dioxide, silicon dioxide and ammonium dihydrogen phosphate is Na3Zr2Si2PO 12 The stoichiometric ratio of the elements.
[0013] Preferably, the ball milling agent includes at least one selected from ethanol, propanol, isopropanol, dichloromethane, ethyl acetate, acetone, and chloroform.
[0014] Preferably, the drying temperature is 50-70° C. and the drying time is 8-12 hours.
[0015] Preferably, during the ball milling process, the mass ratio of the mixed material to the ball milling beads and the ball milling agent is 1:1-30:5-15. The mass ratio of the ball milling beads to the ball milling agent is 3-6:1.
[0016] Preferably, the ball milling process is: ball milling at a speed of 100-2000 r / min for 1-48 h; more preferably, the ball milling process is: ball milling at a speed of 250-1500 r / min for 4-30 h. More preferably, the ball milling speed is 300-1200 r / min for 8-22 h.
[0017] Preferably, the calcination process is: calcination at 100-2500°C for 1-48h; more preferably, the calcination process is: calcination at 500-2000°C for 5-32h. More preferably, the calcination temperature is 1100-1400°C and the calcination time is 8-18h.
[0018] Preferably, the sintering temperature is 500-2000°C; more preferably, the sintering temperature is 800-1700°C.
[0019] Preferably, the sintering time is 1 hour to 48 hours, and more preferably, the sintering time is 4 to 24 hours. More preferably, the sintering temperature is 1200 to 1500° C., and the sintering time is 8 to 18 hours.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention adopts a NASICON precursor Na3Zr2Si2PO 12 Adding POMs (polyoxometalates) materials can effectively improve the sodium affinity and intrinsic ionic conductivity of NASICON solid electrolyte. The interface impedance of the sodium symmetric half-cell prepared by it is less than 20Ωcm at room temperature. 2 , as low as 16.7Ωcm 2 ;
[0022] (2) The present invention provides a method for preparing a high-performance NASICON solid electrolyte material, which has a simple synthesis process and cheap raw materials. In-situ addition (one-step addition) can make NASICON react with additives more uniformly, form a uniform and stable structure, and effectively improve the sodium ion conductivity of the NASICON solid electrolyte.
[0023] (3) The present invention uses a phosphate-based polyanion positive electrode in combination with the high-performance NASICON solid electrolyte material provided by the present invention to prepare a solid-state sodium battery, which can be stably cycled at a high rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the XRD pattern of the NASICON type oxide solid electrolyte sheet obtained in Example 1;
[0025] Figure 2This is a diagram of the sodium ion conductivity of the NASICON type oxide solid electrolyte sheet obtained in Example 1;
[0026] Figure 3 The interface impedance diagram of the NASICON oxide solid electrolyte sheet obtained in Example 1;
[0027] Figure 4 is the XRD pattern of the NASICON type oxide solid electrolyte sheet obtained in Example 2;
[0028] Figure 5 This is a diagram of the sodium ion conductivity of the NASICON-type oxide solid electrolyte sheet obtained in Example 2;
[0029] Figure 6 The interface impedance diagram of the NASICON type oxide solid electrolyte sheet obtained in Example 2;
[0030] Figure 7 is the XRD pattern of the NASICON type oxide solid electrolyte sheet obtained in Example 3;
[0031] Figure 8 This is a diagram of the sodium ion conductivity of the NASICON type oxide solid electrolyte sheet obtained in Example 3;
[0032] Fig. 9 is the interface impedance diagram of the NASICON type oxide solid electrolyte sheet obtained in Example 3;
[0033] Fig.10 is the XRD pattern of the NASICON type oxide solid electrolyte sheet obtained in Example 4;
[0034] Fig.11 This is a diagram of the sodium ion conductivity of the NASICON-type oxide solid electrolyte sheet obtained in Example 4;
[0035] Fig.12 is the interface impedance diagram of the NASICON type oxide solid electrolyte sheet obtained in Example 4;
[0036] Fig.13 is the XRD pattern of the NASICON type oxide solid electrolyte sheet obtained in Example 5;
[0037] Fig.14 This is a diagram of the sodium ion conductivity of the NASICON type oxide solid electrolyte sheet obtained in Example 5;
[0038] Fig.15 is the interface impedance diagram of the NASICON type oxide solid electrolyte sheet obtained in Example 5;
[0039] Fig.16is the XRD pattern of the NASICON type oxide solid electrolyte sheet obtained in Example 6;
[0040] Fig.17 This is a diagram of the sodium ion conductivity of the NASICON-type oxide solid electrolyte sheet obtained in Example 6;
[0041] Fig.18 is the interface impedance diagram of the NASICON type oxide solid electrolyte sheet obtained in Example 6;
[0042] Fig.19 is the XRD pattern of the NASICON type oxide solid electrolyte sheet obtained in Comparative Example 1;
[0043] Fig. 20 This is a sodium ion conductivity diagram of the NASICON type oxide solid electrolyte sheet obtained in Comparative Example 1;
[0044] Fig.21 This is the interface impedance diagram of the NASICON type oxide solid electrolyte sheet obtained in Comparative Example 1. DETAILED DESCRIPTION
[0045] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0046] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0047] The lithium ion conductivity and interface impedance were tested using an electrochemical workstation at room temperature (25°C). The battery cycle performance was tested using a battery charge and discharge tester at room temperature (25°C).
[0048] Example 1
[0049] A high-performance NASICON type oxide solid electrolyte material comprises NASICON and strontium lanthanum aluminate, wherein the added amount of strontium lanthanum aluminate accounts for 0.5% of the mass of NASICON.
[0050] A method for preparing a high-performance NASICON type oxide solid electrolyte material comprises the following steps:
[0051] According to the chemical formula of Na, Zr, Si, P, the stoichiometric ratio is Na3Zr2Si2PO 12Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and lanthanum strontium aluminate were weighed separately and placed in an agate ball mill. The mass ratio of ball mill beads: ball milling agent was 6:1. Ethanol was used as the ball milling agent. The ball mill was milled at a speed of 800 r / min for 20 hours. The mixed slurry was then placed in a 60°C oven and dried for 12 hours to obtain a dry mixed powder. The mixed powder was then sintered at 1200°C for 12 hours to obtain a precursor, which was then pressed into a disc with a diameter of 15 mm and sintered at 1200°C for 8 hours to obtain a high-performance NASICON-type oxide solid electrolyte sheet. After grinding and polishing, the impedance was tested using an electrochemical workstation, and the diffraction pattern was analyzed. The XRD pattern of the high-performance NASICON-type oxide solid electrolyte sheet is shown in the figure. Figure 1 As shown, the result shows a pure NASICON structure; Figure 2 This is the sodium ion conductivity diagram of the high-performance NASICON oxide solid electrolyte sheet, whose sodium ion conductivity reaches 7.4×10 -4 S / cm. At the same time, the interface impedance of the solid electrolyte sheet is 612.7Ω ( Figure 3 ), a solid-state battery with sodium vanadium phosphate as the positive electrode, can be cycled 70 times at 0.2C with a capacity retention rate of 56%.
[0052] Example 2
[0053] A high-performance NASICON type oxide solid electrolyte material comprises NASICON and zinc chromate, wherein the added amount of zinc chromate accounts for 12% of the mass of NASICON.
[0054] A method for preparing a high-performance NASICON type oxide solid electrolyte material comprises the following steps:
[0055] According to the chemical formula, the ratio of Na3Zr2Si2PO 12 Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and zinc chromate were weighed separately and placed in an agate ball mill. The mass ratio of ball mill beads: ball milling agent was 4:1. Propanol was used as the ball milling agent. The ball mill was milled at a speed of 600 r / min for 18 hours. The mixed slurry was then placed in a 60°C oven and dried for 8 hours to obtain a dry mixed powder. The mixed powder was then sintered at 1150°C for 8 hours to obtain a precursor, which was then pressed into a disc with a diameter of 15 mm and sintered at 1300°C for 12 hours to obtain a high-performance NASICON-type oxide solid electrolyte sheet. After grinding and polishing, the impedance was tested using an electrochemical workstation, and the diffraction pattern was analyzed. The XRD pattern of the high-performance NASICON-type oxide solid electrolyte sheet is shown in Figure 2. Figure 4 As shown, the result shows a pure NASICON structure; Figure 5This is the sodium ion conductivity diagram of the high-performance NASICON oxide solid electrolyte sheet, whose sodium ion conductivity reaches 9.2×10 -4 S / cm. At the same time, the interface impedance of the solid electrolyte sheet is 347.5Ω ( Figure 6 ), a solid-state battery with sodium vanadium phosphate as the positive electrode, can be cycled 100 times at 0.2C with a capacity retention rate of 67%.
[0056] Example 3
[0057] A high-performance NASICON type oxide solid electrolyte material comprises NASICON and strontium europium dysprosium aluminate, wherein the added amount of strontium europium dysprosium aluminate accounts for 5% of the mass of NASICON.
[0058] A method for preparing a high-performance NASICON type oxide solid electrolyte material comprises the following steps:
[0059] According to the chemical formula, the ratio of Na3Zr2Si2PO 12 Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and strontium europium dysprosium aluminate were weighed separately and placed in an agate ball mill. The mass ratio of ball mill beads: ball milling agent was 3:1. Isopropanol was used as the ball milling agent. The ball mill was milled at a speed of 700 r / min for 22 hours. The mixed slurry was then placed in a 60°C oven and dried for 12 hours to obtain a dry mixed powder. The mixed powder was then sintered at 1100°C for 8 hours to obtain a precursor, which was then pressed into a disc with a diameter of 15 mm and sintered at 1200°C for 12 hours to obtain a high-performance NASICON-type oxide solid electrolyte sheet. After grinding and polishing, the impedance was tested using an electrochemical workstation, and the diffraction pattern was analyzed. The XRD pattern of the high-performance NASICON-type oxide solid electrolyte sheet is shown in the figure. Figure 7 As shown, the result shows a pure NASICON structure; Figure 8 This is the sodium ion conductivity diagram of the high-performance NASICON oxide solid electrolyte sheet, whose sodium ion conductivity reaches 1.2×10 -3 S / cm. At the same time, the interface impedance of the solid electrolyte sheet is 289.6Ω ( Fig. 9 ), a solid-state battery with sodium vanadium phosphate as the positive electrode, can be cycled 150 times at 0.2C with a capacity retention rate of 81%.
[0060] Example 4
[0061] A high-performance NASICON type oxide solid electrolyte material comprises NASICON and sodium antimonate, wherein the added amount of the sodium antimonate accounts for 10% of the mass of the NASICON.
[0062] A method for preparing a high-performance NASICON type oxide solid electrolyte material comprises the following steps:
[0063] According to the chemical formula, the ratio of Na3Zr2Si2PO 12 Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and sodium antimonate were weighed separately and placed in an agate ball mill. The mass ratio of ball mill beads: ball milling agent was 5:1. Acetone was used as a ball mill. The ball mill was milled at a speed of 300r / min for 8 hours. The mixed slurry was then placed in a 60°C oven and dried for 12 hours to obtain a dry mixed powder. The mixed powder was then sintered at 1300°C for 8 hours to obtain a precursor, which was then pressed into a disc with a diameter of 15 mm and sintered at 1500°C for 12 hours to obtain a high-performance NASICON-type oxide solid electrolyte sheet. After grinding and polishing, the impedance was tested using an electrochemical workstation, and the diffraction pattern was analyzed. The XRD pattern of the high-performance NASICON-type oxide solid electrolyte sheet is shown in the figure. Fig.10 As shown, the result shows a pure NASICON structure; Fig.11 This is the sodium ion conductivity diagram of the high-performance NASICON oxide solid electrolyte sheet, whose sodium ion conductivity reaches 1.4×10 -3 S / cm. At the same time, the interface impedance of the solid electrolyte sheet is 187.1Ω ( Fig.12 ), a solid-state battery with sodium vanadium phosphate as the positive electrode, can be cycled 210 times at 0.2C with a capacity retention rate of 87%.
[0064] Example 5
[0065] A high-performance NASICON type oxide solid electrolyte material comprises NASICON and pyridinium chlorochromate, wherein the amount of lead chromate added accounts for 7.5% of the mass of NASICON.
[0066] A method for preparing a high-performance NASICON type oxide solid electrolyte material comprises the following steps:
[0067] According to the chemical formula, the ratio of Na3Zr2Si2PO 12 Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and pyridinium chlorochromate were weighed separately and placed in an agate ball mill. The mass ratio of ball mill beads: ball milling agent was 6:1. Chloroform was used as the ball milling agent. The ball mill was milled at a speed of 900 r / min for 18 hours. The mixed slurry was then placed in a 60°C oven and dried for 12 hours to obtain a dry mixed powder. The mixed powder was then sintered at 1250°C for 8 hours to obtain a precursor, which was then pressed into a disc with a diameter of 15 mm and sintered at 1350°C for 16 hours to obtain a high-performance NASICON-type oxide solid electrolyte sheet. After grinding and polishing, the impedance was tested using an electrochemical workstation, and the diffraction spectrum was analyzed. The XRD pattern of the high-performance NASICON-type oxide solid electrolyte sheet is shown in the figure. Fig.13 As shown, the result shows a pure NASICON structure; Fig.14 This is the sodium ion conductivity diagram of the high-performance NASICON oxide solid electrolyte sheet, whose sodium ion conductivity reaches 1.8×10 -3 S / cm. At the same time, the interface impedance of the solid electrolyte sheet is 121.7Ω ( Fig.15 ), a solid-state battery with sodium vanadium phosphate as the positive electrode, can be cycled 260 times at 0.2C with a capacity retention rate of 91%.
[0068] Example 6
[0069] A high-performance NASICON type oxide solid electrolyte material comprises NASICON and imidazole dichromate, wherein the added amount of imidazole dichromate accounts for 4% of the mass of NASICON.
[0070] A method for preparing a high-performance NASICON type oxide solid electrolyte material comprises the following steps:
[0071] According to the chemical formula, the ratio of Na3Zr2Si2PO 12 Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and imidazole dichromate were weighed separately and placed in an agate ball mill. The mass ratio of ball mill beads: ball milling agent was 6:1. Ethyl acetate was used as the ball milling agent. The ball mill was milled at a speed of 1200r / min for 12 hours. The mixed slurry was then placed in a 60°C oven and dried for 12 hours to obtain a dry mixed powder. The mixed powder was then sintered at 1400°C for 12 hours to obtain a precursor, which was then pressed into a disc with a diameter of 15 mm and sintered at 1500°C for 18 hours to obtain a high-performance NASICON-type oxide solid electrolyte sheet. After grinding and polishing, the impedance was tested using an electrochemical workstation, and the diffraction pattern was analyzed. The XRD pattern of the high-performance NASICON-type oxide solid electrolyte sheet is shown in the figure. Fig.16 As shown, the result shows a pure NASICON structure; Fig.17 This is the sodium ion conductivity diagram of the high-performance NASICON oxide solid electrolyte sheet, whose sodium ion conductivity reaches 2.4×10 -3 S / cm. At the same time, the interface impedance of the solid electrolyte sheet is 16.3Ω ( Fig.18 ), a solid-state battery with sodium vanadium phosphate as the positive electrode, can be cycled 300 times at 0.2C with a capacity retention rate of 93%.
[0072] Comparative Example 1
[0073] A method for preparing a pure NASICON type oxide solid electrolyte material comprises the following steps:
[0074] According to the chemical formula, the ratio of Na3Zr2Si2PO 12Sodium carbonate, zirconium dioxide, silicon dioxide, and ammonium dihydrogen phosphate were weighed separately and placed in an agate ball mill. The mass ratio of ball mill beads: ball milling agent was 6:1. Ethyl acetate was used as the ball milling agent. The ball mill was milled at a speed of 1200r / min for 12 hours. The mixed slurry was then placed in a 60°C oven and dried for 12 hours to obtain a dry mixed powder. The mixed powder was then sintered at 1400°C for 12 hours to obtain a precursor, which was then pressed into a disc with a diameter of 15 mm and sintered at 1500°C for 18 hours to obtain a high-performance NASICON-type oxide solid electrolyte sheet. After grinding and polishing, the impedance was tested using an electrochemical workstation, and the diffraction pattern was analyzed. The XRD pattern of the pure NASICON-type oxide solid electrolyte sheet is shown in the figure. Fig.19 As shown, the result shows a pure NASICON structure; Fig. 20 This is the sodium ion conductivity diagram of the high-performance NASICON oxide solid electrolyte sheet, whose sodium ion conductivity reaches 4.4×10 -4 S / cm. At the same time, the interface impedance of the solid electrolyte sheet is 947.4Ω ( Fig.21 ), a solid-state battery with sodium vanadium phosphate as the positive electrode, can be cycled 47 times at 0.2C with a capacity retention rate of 42%.
[0075] Comparative Example 2
[0076] The NASICON oxide solid electrolyte material described in Example 6 is prepared by a two-step method: the stoichiometric ratio of Na3Zr2Si2PO 12 Sodium carbonate, zirconium dioxide, silicon dioxide and ammonium dihydrogen phosphate were weighed separately and placed in an agate ball mill. The mass ratio of ball mill beads to ball milling agent was 6:1. Ethyl acetate was used as a ball milling agent. The ball mill was milled at a speed of 1200r / min for 12 hours. The mixed slurry was then placed in a 60°C oven and dried for 12 hours to obtain a dry mixed powder. The mixed powder was sintered at 1400°C for 12 hours to obtain a precursor. Then 4% imidazole dichromate was added to the precursor and ball milled again to dry. It was then pressed into a disc with a diameter of 15 mm and sintered at 1500°C for 18 hours to obtain a NASICON-type oxide solid electrolyte sheet. After polishing, its impedance was tested using an electrochemical workstation. Its sodium ion conductivity reached 3.3×10 -4 S / cm. At the same time, the interface impedance of the solid electrolyte sheet is 1057Ω. It is a solid-state battery with sodium vanadium phosphate as the positive electrode. It can be cycled more than 35 times at 0.2C, and the capacity retention rate is 13%.
Claims
1. A high performance NASICON type oxide electrolyte, characterized in that: The invention takes NASICON type oxide as the matrix and contains 0.1-20 wt% of polyoxometalate of NASICON type oxide.
2. The high performance NASICON type oxide electrolyte according to claim 1, characterized in that: The NASICON type oxide Na3Zr2Si2PO 12 powder.
3. The high performance NASICON type oxide electrolyte according to claim 1, characterized in that: The amount of polyoxometalate added is 0.5%-15wt%; preferably 0.5%-12wt%, more preferably 4-10wt%.
4. The high performance NASICON type oxide electrolyte according to claim 1, characterized in that: The polyoxometalate is at least one selected from strontium lanthanum aluminate, zinc chromate, strontium europium dysprosium aluminate, imidazole dichromate, pyridinium chlorochromate, strontium chromate, sodium antimonate, lead chromate, barium molybdate, sodium molybdate, and zinc tungstate. More preferably, it is strontium europium dysprosium aluminate, pyridinium chlorochromate, imidazole dichromate, and sodium antimonate.
5. The method for preparing a high-performance NASICON-type oxide according to any one of claims 1 to 4, characterized in that: Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and polyoxometalate are weighed to obtain a mixture, a ball milling agent is added, and the mixture is ball-milled to obtain a mixed slurry; the mixed slurry is dried and calcined to obtain a NASICON solid electrolyte precursor, and finally a high-performance NASICON oxide electrolyte is obtained after tableting and sintering.
6. The preparation method according to claim 5, characterized in that: The mass ratio of sodium carbonate, zirconium dioxide, silicon dioxide and ammonium dihydrogen phosphate is Na3Zr2Si2PO 12 The stoichiometric ratio of the elements.
7. The preparation method according to claim 5, characterized in that: The ball milling agent comprises at least one selected from ethanol, propanol, isopropanol, dichloromethane, ethyl acetate, acetone and chloroform.
8. The preparation method according to claim 5, characterized in that: The calcination process is: calcination at 100-2500°C for 1-48h; more preferably, the calcination process is: calcination at 500-2000°C for 5-32h.
9. The preparation method according to claim 5, characterized in that: The sintering temperature is 500-2000° C., and the sintering time is 1 h-48 h.
10. The preparation method according to claim 9, characterized in that: The sintering temperature is 800-1700° C., and the sintering time is 4-24 hours.
Citation Information
Patent Citations
Modified NASICON type oxide ceramic electrolyte as well as preparation method and application thereof
CN114361578A